Ecological distribution of Penaeus schmitti (Dendrobranchiata: Penaeidae) juveniles and adults on the southern coast of Sao Paulo state, Brazil - Barioto, Joao G. [UNESP]; Stanski, Gilson [UNESP]; Grabowski, Raphael C. [UNESP]; Costa, Rogerio C. [UNESP]; Castilho, Antonio L. [UNESP] (Taylor & Francis As, 2017)
This study aimed to describe the ecological distribution and the effects of environmental factor oscillation on the life cycle of Penaeus schmitti along the coastal area of Cananeia, southern Sao Paulo state, Brazil. Shrimp and environmental factors were sampled monthly from July 2012 to May 2014 at seven sampling stations covering both estuarine and marine environments, using a shrimp fishing boat. A total of 273 juveniles and 829 adults were sampled, and there were significant differences in body size (carapace length-CL) throughout the seasons (ANOVA). Smaller animals were observed in the summers of 2013 and 2014 and at sites closer to the coast, which are under estuarine influence. Adults were observed mostly in autumn and in deeper regions. We detected a positive relationship between the abundance of juveniles and the bottom water temperature and between the abundance of adults and the water salinity (canonical correspondence analysis). The presence of smaller individuals in the estuarine environment demonstrates the importance of the estuaries in this species' ontogeny, mainly concerning their protection, since this environment has physical (depth) and physiological (salinity) barriers to their predators. Furthermore, we could clearly observe the plasticity of juveniles in relation to environmental factors. In contrast, adults were less tolerant to the variation in environmental factors, mainly water salinity, which was a limiting factor of their distribution. Seasonal differences in body size could be directly associated to this species' life cycle and characterized by trophic and reproductive migratory activities between the estuarine and oceanic regions.
Keywords: Habitat selection; nursery grounds; Penaeoidea; population dynamics